On the constrained efficiency of strategy-proof random assignment - Christian Basteck; Lars H. Ehlers (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2023)
We study the random assignment of indivisible objects among a set of agents with strict preferences. Random Serial Dictatorship is known to be only ex-post efficient and there exist mechanisms which Pareto-dominate it ex ante. However, we show that there is no mechanism that is likewise (i) strategy-proof and (ii) boundedly invariant, and that Paretodominates Random Serial Dictatorship. Moreover, the same holds for all mechanisms that are ex-post efficient, strategy-proof, and boundedly invariant: no such mechanism is dominated by any other mechanism that is likewise strategy-proof and boundedly invariant.
Keywords: D63; D70; 330; random assignment; strategy-proofness; ex-post efficiency; bounded invariance